2019
DOI: 10.1103/physrevb.99.035107
|View full text |Cite
|
Sign up to set email alerts
|

Lateral interfaces of transition metal dichalcogenides: A stable tunable one-dimensional physics platform

Abstract: We study in-plane lateral heterostructures of commensurate transition-metal dichalcogenides, such as MoS2-WS2 and MoSe2-WSe2, and find interfacial and edge states that are highly localized to these regions of the heterostructure. These are one-dimensional (1D) in nature, lying within the bandgap of the bulk structure and exhibiting complex orbital and spin structure. We describe such heteroribbons with a three-orbital tight-binding model that uses first principles and experimental parameters as input, allowing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 84 publications
(143 reference statements)
1
34
0
Order By: Relevance
“…(+ H.c.), where γ labels the atoms on both sides of the interface. The scaling factor δ describes the compositional symmetry as well as possible relaxation effects at the interface (it is found that δ = 0.1 is a value consistent with experiments [119]). The geometric average, with similar results for the state localization at the interface, uses t as the effective interface hoppings [118].…”
Section: A(b)supporting
confidence: 75%
See 3 more Smart Citations
“…(+ H.c.), where γ labels the atoms on both sides of the interface. The scaling factor δ describes the compositional symmetry as well as possible relaxation effects at the interface (it is found that δ = 0.1 is a value consistent with experiments [119]). The geometric average, with similar results for the state localization at the interface, uses t as the effective interface hoppings [118].…”
Section: A(b)supporting
confidence: 75%
“…where A(B) are the TMDs on either side of the interface. This is analogous to the approach in [119]. Strain tensor.-Recently, the 2D strain tensor in lateral WSe 2 -MoS 2 HSs has been characterized as [36] = aa ab ba bb ,…”
Section: Incommensurability and Strainmentioning
confidence: 90%
See 2 more Smart Citations
“…Transistor structures with TMDC monolayer forming active area in tunnel FETs are being developed [25], also with vertical TMDCs heterostructures [26,27]. The more intriguing lateral, in-plane TMDCs heterojunctions are also constructed, enabling interesting 1D physics at interfaces [28], or leading to improved FETs switching characteristics [29][30][31].…”
Section: Introductionmentioning
confidence: 99%